Front Line Diplomats: African Diplomatic Representations of the Zimbabwean Patriotic Front, 1976–1978. Issue 1 (2nd January 2017) - Scarnecchia, Timothy
Abstract : This article examines front line state (FLS) and Nigerian diplomatic support for the Patriotic Front of Zimbabwe during the crucial years of war and negotiations that ultimately led to independence for Zimbabwe in 1980. The diplomatic role of Nigeria in the process, particularly during 1978, is explored as a contrast to the role of FLS diplomats from Mozambique and Zambia. Based on archival sources from the UK and US, this article presents evidence indicating that while there did exist strong alliances between Joshua Nkomo and his ZAPU party with Zambia and Botswana, and Robert Mugabe's ZANU party counted on the support of Julius Nyerere's Tanzania and Samora Machel's Mozambique, there were periods when these alliances were less than clear cut, and FLS diplomats often defined the relative support provided to each of these parties by the UK and US. The fragile and contested nature of the Patriotic Front alliance between ZAPU and ZANU is analysed as a major stumbling block in independence negotiations, but also as a tool used by Mugabe and Nyerere to influence the outcome of negotiations toward majority rule directly, in order to assure an electoral victory for ZANU.